FIELD APPLICATION OF ANABOLIC STEROIDS IN CARP SEED PRODUCTION II. REARING OF SPAWN TO FRY STAGE - U., BORA; S., RAO P.; K, VENKATESHVARAN (Journal of Indian Fisheries Association, 2015)
Two synthetic androgenic steroids, Ethylestrenol (17 ~ - Hydroxy - 17 aethyl- estr - 4 - en- 3 - one) and Stanozolal (17 ~ -Hydroxy- 17 a -methyl - 5 a -androstano - (3, 2 - C) - pyrazole) were fed via diet at 3 ppm to the spawn ofRohu and Mrigal which were reared upto fry stage over a period of 15 days inearth ern carp nurseries. Both hormones enhanced growth of spawn. A maximumof 25.78% increase in length and 25.69% increase in weight as compared to thecontrols has been recorded. Growth rate was recorded to be 0.8 mm & 2.48 n1g/day (control), and 1.13Inm & 2.67 mg/day (Stanozolol treated) in case ofMrigalspawn; and 0.91 n1m & 2.39 mg/day (control), 1.12 mm & 2.90 mg/day (Ethylestrenoltreated), and 1.10 mm & 2.57 mg/day (Stanozolol treated) in case of Rohuspawn. A decrease in the values of Relative Condition Factor upon hormoneadministration was also noticed.Keywords : anabolic steroids, carp nursery